Dissociating retrieval success from incidental encoding activity during emotional memory retrieval, in the medial temporal lobe - Shafer, Andrea T.; Dolcos, Florin (Frontiers in Behavioral Neuroscience, 2014)
The memory-enhancing effect of emotion, during encoding and retrieval, has been linked to the engagement of emotion- and memory-related medial temporal lobe (MTL) regions (amygdala-AMY; hippocampus-HC; parahippocampus-PHC). However, recognition tasks used to investigate the neural correlates of retrieval make it difficult to distinguish MTL engagement linked to retrieval success (RS) from that linked to incidental encoding success (ES) during retrieval. This issue has been investigated for retrieval of non-emotional memories, but not for emotional memory retrieval. To address this, we used event-related functional MRI with an emotional distraction and two episodic memory tasks (one testing memory for distracter items and the other testing memory for new/lure items presented in the first memory task). This paradigm allowed for dissociation of MTL activity linked to RS from that linked to RS and incidental ES during retrieval. There were two novel findings regarding the neural correlates of emotional memory retrieval. First, greater emotional RS was identified bilaterally in AMY, HC and PHC. However, AMY was most impacted when accounting for ES activity, as only RS activity in left AMY was dissociated from ES activity during retrieval, whereas portions of HC and PHC showing greater emotional RS were largely uninvolved in ES. Second, an earlier and more anteriorly spread response (left AMY and bilateral HC, PHC) was linked to greater emotional RS, whereas a later and more posteriorly localized response (right posterior PHC) was linked to greater neutral RS. These findings shed light on MTL mechanisms subserving the memory-enhancing effect of emotion at retrieval.